INTERACTIONS BETWEEN (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])[sub]2[/sub]SnPh2•H[sub]2[/sub]O AND SnC[sub]l2[/sub]•2H[sub]2[/sub]O: (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])[sub]2[/sub]SnPh[sub]2[/sub]•2SnCl[sub]4[/sub] OR (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])[sub]2[/sub]SnCl[sub]2[/sub]•2SnPhCl[sub]3[/sub] ? THE MÖSSBAUER EFFECT SOLUTION - Libasse Diop; Hayat Qamar Kane (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The study of the interactions between (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])SnPh[sub]2[/sub]•H[sub]2[/sub]O and SnCl[sub]2[/sub]•2H[sub]2[/sub]O in EtOH has yielded a trinuclear adduct which Mössbauer study has allowed to choose (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])[sub]2[/sub]SnCl[sub]2[/sub]•2SnPhCl[sub]3[/sub] rather than (Me[sub]4[/sub]N)[sub]2[/sub](C[sub]2[/sub]O[sub]4[/sub])[sub]2[/sub]SnPh[sub]2[/sub]•2SnCl[sub]4[/sub] for formula, the oxalate anion behaving as a bichelating ligand, the environment around the tin (IV) centre being octahedral.